2019
DOI: 10.1016/j.ijrefrig.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of heat pumps for simultaneous heating and cooling using CO2

Abstract: Highlights  A model of a CO2 heat pump is described  A first model simulates a heat pump for simultaneous heating and cooling  A second model simulates a heat pump for simultaneous cooling and desalination  CO2 proposes new interesting applications for multi-function heat pumps

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
(25 reference statements)
0
18
0
Order By: Relevance
“…The authors performed a numerical study to compare this heat pump architecture operating with CO 2 and with R407C, and observed that CO 2 can outperform the HFC in terms of environmental impact. Diaby et al (2019) [24] is a continuation of the previous work, as the authors present heat pump models for either simultaneous cooling, SH, and DHW or desalination. The numerical results in both cases are satisfactory, and the authors conclude that CO 2 is an exceptionally suited refrigerant for multipurpose heat pumps compared to "standard" refrigerants.…”
Section: Introductionmentioning
confidence: 92%
“…The authors performed a numerical study to compare this heat pump architecture operating with CO 2 and with R407C, and observed that CO 2 can outperform the HFC in terms of environmental impact. Diaby et al (2019) [24] is a continuation of the previous work, as the authors present heat pump models for either simultaneous cooling, SH, and DHW or desalination. The numerical results in both cases are satisfactory, and the authors conclude that CO 2 is an exceptionally suited refrigerant for multipurpose heat pumps compared to "standard" refrigerants.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, the potential interest of coupling MD with a heat pump for simultaneous cooling of residential and commercial buildings and clean water production was demonstrated [9,47]. It is estimated that 17% of the global electric energy is consumed by the four billion air conditioning and refrigeration devices installed worldwide [3].…”
Section: Heat Pumps For Desalinationmentioning
confidence: 99%
“…A good example of where thin-walled pipes are vital is in the use of high pressure refrigeration systems, such as two-phase CO 2 cooling. CO 2 is a particularly attractive refrigerant as it is a non-toxic, non-flammable gas that does not contribute to ozone depletion [3] and is significantly cheaper than fluorocarbons. Two-phase CO 2 cooling exploits the latent heat change of the liquid to gas transition in order to generate a cooling effect.…”
Section: High Pressure Cooling Systemsmentioning
confidence: 99%